2021
DOI: 10.22541/au.161011517.73852429/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combining range and phenology shifts offers a winning strategy for boreal Lepidoptera

Abstract: Species can adapt to climate change by adjusting in situ or by dispersing to new areas, and these strategies may complement or enhance each other. Here, we investigate temporal shifts in phenology and spatial shifts in northern range boundaries for 289 Lepidoptera species by using long-term data sampled over two decades. While 40% of the species neither advanced phenology nor moved northward, nearly half (47%) -used one of the two strategies. The strongest positive population trends was observed for the minori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 63 publications
1
15
2
Order By: Relevance
“…Overall, our findings contrast with the expected pattern of phenological advancement under a global warming scenario [1,5]. Indeed, recent work based on similar data and lengths of time series to our study supports the idea that in recent decades, phenological advancements may not have been as common as predicted [13]. Only 8% of the species in our dataset underwent significant advances and, surprisingly, 15% of the species in fact delayed their phenology.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Overall, our findings contrast with the expected pattern of phenological advancement under a global warming scenario [1,5]. Indeed, recent work based on similar data and lengths of time series to our study supports the idea that in recent decades, phenological advancements may not have been as common as predicted [13]. Only 8% of the species in our dataset underwent significant advances and, surprisingly, 15% of the species in fact delayed their phenology.…”
Section: Discussioncontrasting
confidence: 88%
“…In the UK, Macgregor et al . [12] found a positive effect for phenological advancement on abundance trends, but as in our work, this effect has not been found in other regions [13,30]. The effect in the UK was only found for multi-voltine species, so the relatively small number of multi-voltine species in our study dataset after removing the multi-voltine species with overlapping generations ( n = 16) in comparison to the dataset of Macgregor et al .…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Our findings on phenological shifts can be situated in a broader context of ecological responses to climate change, including phenological, distributional, and physiological responses (Hällfors et al., 2021). Apart from plant phenology, recent studies on plant migration and productivity have also shown lags in biotic responses to climate change.…”
Section: Discussionmentioning
confidence: 70%
“…In Finland, for example, 30.3% of the assessed Lepidoptera taxa (n = 716) are red listed (Hyvärinen et al 2019). In comparison to central European countries, however, Lepidoptera in Nordic countries, such as Finland, are still doing relatively well (Hällfors et al 2021).…”
Section: Introductionmentioning
confidence: 97%